Spatial reawakening: Transformation of abandoned spaces in rural landscapes through architectural explorations - Vertetics, Elin (My University, 2025)
The thesis explores the concept of spatial reawakening by analysing the relationship between the landscape as found and its constructed assemblages. The term assemblage in the thesis refers to all built structures within a context or landscape. By exploring the necessary degree of architectural intervention required to define space, the thesis contributes to broader discussions on spatial qualities. The rural stone-cutting landscape of the Stone Coast on north-western Öland serves as an experimental ground for explorations. Here, interventions are tested for their ability to interact with and enhance the spatial and cultural significance of the site. The existing spatial qualities of the landscape are explored through drawings, maps, photographs and literature. Strategies for spatial reawakening are explored through an iterative process, where the landscape is both adjusted by reconfiguring on-site materials and enhanced through the integration of local material resources. The thesis uncovers a process for architectural interventions that fosters a dynamic interaction between the landscape as found and its assemblages, ensuring that neither dominates the other. The process is informed by interdisciplinary theories on spatial qualities, reawakening strategies, and local context. While the themes of identity, heritage and spatial perception are central to the work, the thesis acknowledges their inherently subjective interpretations. The thesis is structured through four key phases, (1.) Mapping, (2.) Exploration, (3.) Reawakening and (4.) Discussion. Each phase implements methods and tools specifically designed to achieve its respective objectives. The design process supports a design strategy of minimal intervention, rooted in the traditions of local craftsmanship and sensitivity. The interventions and reawakening strategies critically engage with traditional building practices, promoting a more integrated and a design approach with a high level of responsiveness. The final design proposal should be considered as a culmination of the previous phases, with the chosen site serving primarily as a experimental platform.
Keywords: Spatial qualities, Reawakening, Landscape, Exploration, Limestone